Disruptive Mood Dysregulation Disorder in A Primary School Sample - ERDOĞDU, AYŞE BURCU; GÖKSU, MUHSİNE (ELSEVIER, 2020)
Objective: This study aimed to determine frequency of DMDD in a community-based sample and to identify comorbid diagnoses in children with DMDD. Methods: The Child Behavior Checklist was given to 650 children attending the primary school and 453 children constituted the sample of the study. 83 children with a total score of 180 in CBCL attention, anxious/depression and aggression subscale scores were evaluated as moderate risk group (MRG) and 14 children with a total score of 210 and higher were considered as high-risk group (HRG) in terms of DMDD. 30 (6.62%of the study sample) from MRG and HRG agreed to participate in the study. DSM-V based psychiatric interview (PI) was done by a child and adolescent psychiatrist. Results: Eight of 30 children who underwent PI were within the high-risk group (HRG), and 4 of these children were diagnosed with DMMD (0.88% of the total sample). There was at least one comorbid diagnosis in all four children diagnosed with DMMD. Conclusions: Our study is one of the few studies evaluating the frequency of DMMD in Turkey. Although the prevalence of DMMD is low, comorbid diagnosis rates require detailed examination and multifaceted perspectives in the follow-up and treatment process.
Keywords: Mood dysregulation; Children; Comorbidity; Fequency; OPPOSITIONAL DEFIANT DISORDER; BEHAVIORAL-DISORDERS; COMORBIDITY; ADOLESCENT; CHILD; AGE; PSYCHOPATHOLOGY; IRRITABILITY; PREVALENCE; PREDICTORS